2015
DOI: 10.1016/j.sbspro.2015.01.916
|View full text |Cite
|
Sign up to set email alerts
|

Using Comics with Novice EFL Readers to Develop Reading Literacy

Abstract: The study concentrated on the possible effects of using authentic comics with EFL learners. It examined the strategies applied by novice readers in reading comics with the special focus on lexical guessing using context. The data for this illustrative qualitative case study were collected from observations, discussions, verbal report and in some cases students' writings. The results indicated possible positive effects in vocabulary development and motivation to reading and overcoming linguistic barriers in rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 6 publications
5
35
0
5
Order By: Relevance
“…Thirdgrade students of elementary school like colorful pictures as they find in illustration in comic. Scott McCloud (in Cimermanová, 2015) describes that comic is juxtaposed pictorial and other images in deliberately constructed in sequence to convey information and/or to produce aesthetic response from the readers [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thirdgrade students of elementary school like colorful pictures as they find in illustration in comic. Scott McCloud (in Cimermanová, 2015) describes that comic is juxtaposed pictorial and other images in deliberately constructed in sequence to convey information and/or to produce aesthetic response from the readers [4].…”
Section: Introductionmentioning
confidence: 99%
“…L2 writing scholars have agreed that the foreign language context is fundamentally different, in the sense that there is little access to the target language in the surrounding environment and that the purpose for developing literacy skills is often unclear (Leki, 2001;Reichelt, Lefkowitz, Rinnert, & Schultz, 2012). As a result, foreign language literacy is often discussed in relation to language acquisition and linguistic development (Cimermanová, 2015;Fukunaga, 2006;Warner & Dupuy, 2018). For example, Fukunaga's (2006) study on Japanese as foreign language learners suggested that reading animes could contribute to the development of word recognition, listening skills, pronunciation, and cultural awareness.…”
Section: Research On L2 Literacymentioning
confidence: 99%
“…In contrast, a large part of the existing discussion on EFL literacy is situated in instructional settings and constrained within the scheme of language development (e.g., Cimermanová, 2015), thus downplaying the interactive, dynamic, and social nature of literacy in a digital era. The literature of the second language (L2) and literacy education hence points to the need for more studies on multilingual users' multiple forms of meaning-making in various contexts (Dagenais, Toohey, Bennett, & Singh, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Alanyazındaki araştırmalara bakıldığında çizgi romanlara ilişkin bazı çalışmaların bulunduğu (Akkaya, 2013;Başal, Aytan ve Demir, 2016;Topkaya, 2016) ve eğitici çizgi romanların öğrenme öğretme süreçlerinde yararlanılabilecek kaynaklardan biri olduğu araştırmacılar tarafından ifade edilmektedir (Başol, 2011;Cimermanová, 2015;Graham, 2011;Öz ve Efecioğlu, 2015;Rajendra, 2015;Swai, 1978). Buna karşılık alanyazında Adam Olmuş Çocuklar ile Kahraman Kadınlarımız eğitici çizgi roman dizilerinin disiplinler arası içeriklerini belirlemeyi ve bunları okuduğunu anlama stratejileri ile ilişkilendirmeyi amaçlayan herhangi bir çalışmaya rastlanmamıştır.…”
Section: Eğitici çIzgi Roman Ve Disiplinler Arası İlişkilerunclassified